Patient preferences for atopic dermatitis treatments: a discrete choice experiment - Shawn G. Kwatra; Peter Lio; Stephan Weidinger; Brian Calimlim; Barry Ladizinski; Namita Vigna; Willings Botha; Carol Mansfield (Taylor & Francis Group, 2023)
Background Patients with moderate-to-severe atopic dermatitis (AD) experience skin lesions and intense itch that substantially affect quality of life. Patients have choices among systemic AD treatments that offer varied benefit-risk profiles. Objective Measure patients' willingness to trade off the risks and benefits of systemic treatments among individuals with a physician-confirmed diagnosis of moderate-to-severe AD. Methods Patients participated in a discrete choice experiment online survey with a series of choices between hypothetical AD treatments defined by six attributes reflecting benefits and risks of treatments (itch reduction, time until noticeable itch reduction, chance of clear or almost clear skin, risk of serious infection, risk of developing acne, and need for prescription topical steroids). Data were analyzed with a random parameters logit model to quantify preferences and the relative importance of attributes for treatment alternatives. Results Respondents (n = 200) placed the highest relative importance on itch reduction, speed of itch reduction, and skin clearance, and were generally willing to accept clinically relevant levels of risk of serious infection and acne in exchange for treatment benefits. Conclusions Patients with moderate-to-severe AD were willing to trade clinically relevant treatment risks for greater or more rapid itch reduction and skin clearance offered by systemic therapies.